A sports practitioner`s perspective on the Return to Play during the early months of the COVID-19 pandemic: Lessons learned and next steps - Chiampas, G. T.; Chenworth, M. L.; Power, E.; Ibiebele, A. L. (Sports Science Exchange, 2021)
Key Points: